(untitled) - Douglas L Vermillion (Rome, 1999)
These guidelines have written to assist policy-makers, technical assistance experts and other stakeholders to dicide whether or not to dropt irrigation management tranfer, and if so, how to formulate an effective programme. An effective programme is one that results in approciate, successful and sustainable devolution of roles from the irrigation agency to wtaer user's groups and fosters equipment in rural areas.
Keywords: irrigation